Income Disparities in the Platform-Based Economy: An Analysis of Technology Access and its Implications for Digital Inequality - Maria Wati (PT. Berkah Smart Academica, 2024)
This research analyzes digital economic inequality and its impact on income disparity within the platform-based economy era. Through a comprehensive literature review, the study identifies factors contributing to unequal technology access, including infrastructure, digital skills, and socioeconomic aspects. The findings indicate that disparities in technology access significantly limit income-generating opportunities, particularly within the platform economy context. Furthermore, low digital literacy exacerbates this gap, and the platform economy itself can worsen income disparities if workers lack adequate protection. This study contributes to a deeper understanding of the complex dynamics among technology, income, and social inequality. The research findings underscore the urgent need for policies that promote equitable technology access, enhance digital skills, and ensure protection for platform workers.